Health-related characteristics and preferred methods of receiving health education according to dominant language among Latinos Aged 25 to 64 in a large Northern California health plan - Iribarren Carlos; Gordon Nancy P (BMC, 2008)
Abstract Background Latinos are a fast growing segment of the U.S. health care population. Acculturation factors, including English fluency, result in an ethnic group heterogeneous with regard to SES, health practices, and health education needs. This study examined how demographic and health-related characteristics of Spanish-dominant (SD), Bilingual (BIL), and English-dominant (ED) Latino men and women aged 25-64 differed among members of a large Northern California health plan. Methods This observational study was based on data from cohorts of 171 SD (requiring an interpreter), 181 BIL, and 734 ED Latinos aged 25-64 who responded to random sample health plan member surveys conducted 2005-2006. Language groups were compared separately by gender on education, income, behavioral health risks (smoking, obesity, exercise frequency, dietary practices, health beliefs), health status (overall health and emotional health, diabetes, hypertension, high cholesterol, heartburn/acid reflux, back pain, depression), computer and Internet access, and health education modality preferences. Results Compared with ED Latinos, higher percentages of the SD and BIL groups had very low educational attainment and low income. While groups were similar in prevalence of diabetes, hypertension, and high cholesterol, SD were less likely than ED Latinos to rate overall health and emotional well-being as good, very good, or excellent and more likely to report heartburn and back pain (women only). The groups were similar with regard to smoking and obesity, but among women, SD were more likely to be physically inactive than ED, and BIL were less likely than SD and ED groups to eat <3 servings of fruit/vegetables per day. SD and BIL of both genders were significantly less likely than ED Latinos to believe that health practices had a large impact on health. Compared to ED men and women, SD and BIL Latinos had significantly lower Internet and computer access. As a result, SD Latinos had a greater preference for lower technology health education modalities such as videos and taped phone messages. Conclusion There are important differences among Latinos of different English language proficiency with regard to education, income, health status, health behaviors, IT access, and health education modality preferences that ought to be considered when planning and implementing health programs for this growing segment of the U.S. population.